If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 6y = 16 Solving 10x + 6y = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 10x + 6y + -6y = 16 + -6y Combine like terms: 6y + -6y = 0 10x + 0 = 16 + -6y 10x = 16 + -6y Divide each side by '10'. x = 1.6 + -0.6y Simplifying x = 1.6 + -0.6y
| -7x^2-18x+0=0 | | 2z-67=-21 | | 8-(-4)+5=12 | | 7n+3-5n=3n-6 | | V=3.14v^2h | | (25)(7)+x=175 | | -3x+6x=0 | | 0=5x^2-64x-13 | | 18+5=48 | | x-29=15 | | .5(12x-8)=9x-18 | | 5x-3-2x=2(x-4) | | 3(x+2)=5(x-1)+5 | | 0=2a^2+7a+3 | | 4(5y-3)-(8y+5)= | | 2x+5(6x-4)=44 | | 40(25+x)=1 | | 8x-14=3x-6 | | m+90=150 | | -16x^2+324=0 | | 9x+6=6x+4 | | 0=-15m^2+60 | | 8(4+x)=360 | | 10x+7=8x-6 | | 21-12=3(x-8) | | 2x-(x-1)=3+x | | .75x-16=2(x-3)+4 | | 8(4+x)=72.00 | | 6n-3+2n=-1 | | 20(4r-48)= | | 2x+3-2x=2x+7 | | 7(x+1)=6(x-3) |